(Table 1) Organic carbon, nitrogen and sulphur concentrations and δ¹³C of TOC from ODP Hole 167-1017E sediments - Ishiwatari, Ryoshi; Matsumoto, Kohei; Seki, Osamu; Yamamoto, Shuichi (Supplement to: Ishiwatari, R et al. (2000): Variations in organic carbon isotopic composition in sediments at Site 1017 during the last 25 k.y. In: Lyle, M; Koizumi, I; Richter, C; Moore, TC Jr (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 167, 1-4, https://doi.org/10.2973/odp.proc.sr.167.210.2000, 2000)
A high-resolution analysis of Hole 1017E revealed that total organic carbon (TOC) concentrations (24.8 ± 2.9 mg/g) and d13C of TOC (-21.3 ± 0.2 per mil) in Holocene sections are higher than those in glacial sediments (14.2 ± 4.8 mg/g and -22.1 per mil ± 0.1 per mil, respectively). The 306- to 280-cm section has high total sulfur concentrations, which may correspond to anoxia Event 1 (1 of the warm interstadials of GISP2) in the Santa Barbara Basin.